329 SUN EXPOSURE AND PROTECTION EDUCATION FOR PATIENTS IN ODESSA, WASHINGTON. Issue 1 (1st January 2007) - Shepherd, A.
Abstract : Purpose of Study: The population of Odessa, Washington, is largely composed of individuals of European descent who are thus at high risk for developing skin cancers. Many individuals have outdoor occupations that require significant hours in the sun. Methods: An educational approach was devised to target school-aged children. Most lifetime exposure to harmful radiation occurs before the age of 18, and this group is most likely to alter their protective behaviors with education. Brochures were produced that included information to assess risk factors, investigate effective protective measures, illustrate examples of lesions, and discount common misconceptions. Eighteen brochures were given to children and adolescents between the ages of 8 and 16 during school-sports physicals. Each patient was counseled about current knowledge and protective behaviors. Parents were encouraged to participate and their concerns were addressed. Results: Sun-protective behaviors were not currently used by the majority because this age group did not know the dangers involved, did not understand the proper way to use sun protection, or forgot to use protection. Patients demonstrated overall increased knowledge after the consultation. Parents were provided information regarding better protection. Brochures were also given to hospital and clinic staff to distribute. Conclusions: By increasing the education of this group about the seriousness of sun exposure and by providing parents with information on how to best protect their children, protective behaviors are more likely to be practiced.